2021
DOI: 10.2196/28568
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Response to the Pfizer-BioNTech COVID-19 Vaccine Measured Using Wearable Devices: Prospective Observational Study

Abstract: Background The Pfizer-BioNTech COVID-19 vaccine uses a novel messenger RNA technology to elicit a protective immune response. Short-term physiologic responses to the vaccine have not been studied using wearable devices. Objective We aim to characterize physiologic changes in response to COVID-19 vaccination in a small cohort of participants using a wearable device (WHOOP Strap 3.0). This is a proof of concept for using consumer-grade wearable devices to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Importantly, rather than relying on participant-reported side effects, our study assessed objective (continuously assessed) physiological measures as predictors of vaccine responses. Data presented here speak to recent calls for examining wearable device data in tandem with immune responses to vaccines [12]. The continuous predictors in these analyses may have been more sensitive to the effects of vaccination in generating systemic inflammatory responses.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Importantly, rather than relying on participant-reported side effects, our study assessed objective (continuously assessed) physiological measures as predictors of vaccine responses. Data presented here speak to recent calls for examining wearable device data in tandem with immune responses to vaccines [12]. The continuous predictors in these analyses may have been more sensitive to the effects of vaccination in generating systemic inflammatory responses.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, we tested whether a wearable device (Oura Ring), which collects data on dermal temperature, heart rate, heart rate variability, and various sleep metrics (total sleep duration, deep sleep duration, and rapid eye movement (REM) sleep duration) could be used to detect the early period of COVID-19 disease. Prior data suggest that wearable devices can detect changes in physiology that follow mRNA vaccination against COVID-19 [12]. Most participants received a COVID-19 vaccine during the study.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no narcolepsy-related disorder case report is related to COVID-19 vaccination. There is a recent proof-of-concept study using wearable devices found an increased sleeping duration up to four days post-BNT162b2 vaccination [ 53 ]. The sleeping signal detected in this study encourages further investigation on the immunogenicity, mechanism and association between mRNA vaccine and sleeping disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Wearable device data is increasingly used in large studies across several fields of medicine. Another example is the tracking of HRV, resting heart rate, and respiratory rate as a measurement of tolerance in patients after receiving the Pfizer-BioNTech COVID-19 vaccine [47].…”
Section: Discussionmentioning
confidence: 99%
“…By requiring standards of third-party validation of these devices in real-world settings, we can continue to allow data collected by smart watches to play an increasing role in our medical decision making, specifically related to the detection and monitoring of conditions, and trial designs [47,49]. Consumer-available devices present an ever-changing and exciting field of possibilities, especially in the cardiac patient [50].…”
Section: Sleep Cycle Trackingmentioning
confidence: 99%